Current and future methods of probiotic therapy for necrotizing enterocolitis - Sajankila, Nitin; Wala, Samantha Jane; Ragan, Mecklin Victoria; Volpe, Samuel Grant; Dumbauld, Zachary; Purayil, Nanditha; Mihi, Belgacem; Besner, Gail E. (Frontiers in Pediatrics, 2023)
Necrotizing enterocolitis (NEC) is a complex intestinal disease that primarily affects premature neonates. Given its significant mortality and morbidity, there is an urgent need to develop improved prophylactic measures against the disease. One potential preventative strategy for NEC is the use of probiotics. Although there has been significant interest for decades in probiotics in neonatal care, no clear guidelines exist regarding which probiotic to use or for which patients, and no FDA-approved products exist on the market for NEC. In addition, there is lack of agreement regarding the benefits of probiotics in neonates, as well as some concerns about the safety and efficacy of available products. We discuss currently available probiotics as well as next-generation probiotics and novel delivery strategies which may offer an avenue to capitalize on the benefits of probiotics, while minimizing the risks. Thus, probiotics may still prove to be an effective prevention strategy for NEC, although further product development and research is needed to support use in the preterm population.